2011
DOI: 10.1097/mou.0b013e3283476ea2
|View full text |Cite
|
Sign up to set email alerts
|

The afferent system and its role in lower urinary tract dysfunction

Abstract: Recent studies provide further evidence that afferent control of the bladder may be dependent on integration of excitatory and inhibitory mediators from the urothelium such as ATP and nitric oxide. A number of studies have examined the role cholinergic and adrenergic mechanisms play in bladder afferent function, and several new potential mechanisms involving the cannabinoid receptors and transient receptor potential channels have emerged as areas which warrant further investigation. A better understanding of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 55 publications
(41 reference statements)
4
33
0
1
Order By: Relevance
“…While urothelium has historically been viewed as a simple barrier separating the bladder wall from urine, increasing evidence also suggests that the urothelial cells play a critical role in physiological and pathophysiological processes in the bladder (Daly et al, 2011; Birder and Andersson, 2013; Hill, 2014; Keay et al, 2014; Gonzalez et al, 2014). Specifically, urothelial cells have the capacity to secrete a variety of signaling molecules such as PGE 2 , NGF, nitric oxide, and cytokines in response to various stimuli (Malley and Vizzard, 2002; Wang et al, 2008; Birder and Andersson, 2013; Hill, 2014; Keay et al, 2014; Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While urothelium has historically been viewed as a simple barrier separating the bladder wall from urine, increasing evidence also suggests that the urothelial cells play a critical role in physiological and pathophysiological processes in the bladder (Daly et al, 2011; Birder and Andersson, 2013; Hill, 2014; Keay et al, 2014; Gonzalez et al, 2014). Specifically, urothelial cells have the capacity to secrete a variety of signaling molecules such as PGE 2 , NGF, nitric oxide, and cytokines in response to various stimuli (Malley and Vizzard, 2002; Wang et al, 2008; Birder and Andersson, 2013; Hill, 2014; Keay et al, 2014; Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of PCR product was determined semi-quantitatively using a standard curve for each gene. Relative abundance of mRNA in the mucosa was assessed for substances that have been reported to play significant roles in pain and inflammation, including nerve growth factor (NGF), cyclooxygenase-2 (COX-2), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), endothelial nitric oxide synthase (eNOS) and inducible nitric oxide synthase (iNOS) (Malley and Vizzard, 2002; Wang et al, 2008; Daly et al, 2011; Birder and Andersson, 2013; Keay et al, 2014; Gonzalez et al, 2014). Expression of each gene was normalized to abundance of mRNA for L19, a constitutively-expressed ribosomal protein in the same sample.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, atherosclerosis-induced chronic ischemic bladder also decreased constitutive nitric oxide synthase (NOS) (20). Since reports have shown that nitric oxide has both relaxatory and facilitatory effects, as well as having direct effects on the detrusor and modulatory effects via the afferent nerves, it has been suggested that the effect of the nitric oxide on the afferent nerve signaling occurs primarily in an inhibitory fashion (4). The decrease of urinary NOx in the pelvic venous congestion rats examined in the present study might indicate that bladder tissue hypoxia is one of causes of the alterations in the urinary frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The urothelium must also communicate information to the underlying sensory nerve fibers to reflect its degree of physical distension, so that both sympathetic and parasympathetic neurons can coordinate their activities to ensure synchronized detrusor smooth muscle contraction and urethral relaxation (17). One of the key neurotransmitters released by the urothelium in response to hydrostatic pressure induced stretch is ATP (21,42,80).…”
Section: Function Of the Urotheliummentioning
confidence: 99%